Subtalar fusion with iliac bone free flap after a recalcitrant nonunion: Report of two cases. Issue 6 (12th October 2015) - Roger, Ignacio; Worden, Alicia; Panattoni, Joao; Garcia, Ignacio; Aranda, Fernando; Delgado, Paula A.
Abstract : Fractures of the calcaneus are associated with secondary osteoarthritis of the subtalar joint. In a persistent nonunion, vascularized bone flaps offer superior biologic and mechanical properties as well as accelerates joint fusion and decreases morbidity. In this report, we present results of the use of vascularized iliac bone free flap for treating subtalar failed fusions in two patients. Two patients sustained calcaneal fractures due to foot trauma, which were initially or subsequently treated with subtalar arthrodesis. Case one developed septic subtalar nonunion during treatment and case two failed three attempts at subtalar arthrodeses. The iliac crest bone flap harvested measured 4 × 4 cm (case one) and 3 × 3 cm (case two). The flap was pedicled by the deep circumflex iliac artery, which was anastomosed to the anterior tibial artery at the recipient site. No flap donor or recipient site complications occurred. Fusion was confirmed on CT scan and weight bearing was initiated at 5–6 months. At latest follow up (1–2 years), no complications occurred. Our results show that subtalar nonunion treatment with a vascularized iliac bone flap may be feasible and such a reconstruction could be clinically successful. © 2015 Wiley Periodicals, Inc. Microsurgery 36:501–506, 2016.